Mise- en- scène e personagem em a árvore da miséria de Marcus Vilar - Palitot, João Paulo Feitoza Clementino (2016)
This dissertation's goal is to analyze the movie "A árvore da miséria" (The tree of misery) (VILAR, 1998), giving special attention to the mise-en-scène (stage setting) and character categories since those were the main parts of the film building process. The correlation between stage setting and character is also one of the issues of this work. The reason is that the relocation of the actors bodies at the scene is necessary for the full development of the stage setting category (BORDWELL; THOMPSON, 2013). The fact that our object of study is a film version of the literature, written by Fernando Ferreira, will also be a point of attention. The study of the dialogue between these two forms of art (HUTCHEON, 2011) seeks to understand the exchanges between literary and audiovisual objects.